Analisis Yuridis terhadap Implementasi Undang-Undang Nomor 8 Tahun 2015 dalam Strategi KPU Meningkatkan Partisipasi Pemilih Muda pada Pilkada Serentak - Imroatul Hasanah; Ilham Ilham; Nanda F; Zilda Khilmatus Shokhikhah (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study examines the implementation of Law Number 8 of 2015 within the context of the General Election Commission's (KPU) strategy to increase young voter participation in simultaneous regional elections (Pilkada). Employing a normative juridical research method with a statutory approach, this analysis investigates the legal basis and KPU's strategies in efforts to enhance young voter engagement. The research findings indicate that Law No. 8/2015 and PKPU No. 8/2017 provide a comprehensive legal basis for the KPU to implement strategies for increasing young voter participation through various programs such as school-based socialization, social media campaigns, and collaborations with youth organizations and educational institutions. Factors influencing the effectiveness of these strategies include internal aspects such as human resources, knowledge management, and financial support, as well as external factors such as public political awareness, effective communication, and public response. This research concludes that while the legal framework is adequate, more detailed regulations regarding young voters are still needed, and the strategies implemented by the KPU are in line with existing laws.